Anatomical arrangement of the lobar bronchi, broncho- pulmonary segments and their variations - K., Sathidevi V. (International Journal of Research in Medical Sciences, 2016)
Background: The segmental concept of lungs was still in dispute in the literature. Although the segments differ considerably in shape and size, they all contain a well-defined area of lung and they are all well demarcated from the neighbouring segments. Therefore, in the present study, an attempt has been made to demonstrate the anatomical arrangement of the lobar bronchi, broncho-pulmonary segments and their variations. Methods: The study was conducted in fifty human lungs, obtained from autopsies, dissection hall cadavers and full term foetuses. The bronchial tree was investigated by air inflation, dye injection and using dissection, preparation of casts, air inflation, dye injection and bronchographic techniques. The external morphology of lungs and their lobes has been studied and the bronchopulmonary segments are described in detail. Results: In humans, the right lung is found to consist of ten segments in only 77% cases, and the left lung of ten segments in 84% cases. Thus in the study of 50 human lungs, the classical textbook description has occurred only in 80.5% of cases. Remaining 19.5% showed variations. Among the variations observed, right lung showed (59%) predominance over (41%) on left side. Conclusions: In man there is an increase in the number of bronchial generations and alveoli after birth. An increase in their size was noted as well. Thus the study of variations in the pattern of bronchopulmonary segments aids the clinician very much. It is necessary for Thoracic Surgeons, Anaesthetists, Chest physicians, Radiologists, Ultrasonologists, Pathologists and Anatomists for investigative procedures, diagnosis and various treatment modalities including surgeries like segmentectomy.